2005
DOI: 10.1136/adc.2005.073866
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a divided high loading dose of caffeine on circulatory variables in preterm infants

Abstract: Background: A single high loading dose of 25 mg/kg caffeine has been shown to be effective for the prevention of apnoea, but may result in considerable reductions in blood flow velocity (BFV) in cerebral and intestinal arteries. Objective: To assess the effects of two loading doses of 12.5 mg/kg caffeine given four hours apart on BFV in cerebral and intestinal arteries, left ventricular output (LVO), and plasma caffeine concentrations in preterm infants. Design: Sixteen preterm neonates of ,34 weeks gestation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 34 publications
4
32
0
Order By: Relevance
“…Hoecker et al 4,6 examined the effect of caffeine loading in two regimens in two groups of 16 infants and showed no change in left ventricular CO (LVCO), HR or BP when measured 1 and 2 h after in one regimen and 1, 2 and 20 h later in the second regimen. Walther et al 5 showed an increase in LVCO and HR in 11 infants treated with aminophylline, however postaminophylline determinations were made 4 h after maintenance dose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hoecker et al 4,6 examined the effect of caffeine loading in two regimens in two groups of 16 infants and showed no change in left ventricular CO (LVCO), HR or BP when measured 1 and 2 h after in one regimen and 1, 2 and 20 h later in the second regimen. Walther et al 5 showed an increase in LVCO and HR in 11 infants treated with aminophylline, however postaminophylline determinations were made 4 h after maintenance dose.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] However, caffeine has other physiologic effects, including stimulating the central nervous and cardiovascular system, 4 enhancing catecholamine secretion, 4 and increasing basal metabolic rate. 4 At the pharmacologic level, caffeine acts by blocking adenosine receptors A1 and A2a, increasing cyclic 3, 5 adenosine monophosphate by inhibiting phosphodiesterase, and translocating intracellular calcium. 5 At least plausibly, some of these pharmacologic actions might interact with regulation of systemic hemodynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Hoecker et al (27) reported an increase in arterial pressure in preterm infants, 1 and 20 h after day 2 of caffeine administration, and an increase in heart rate 20 h after day 2 of caffeine exposure. However, these increases were compared with measurements taken just prior to caffeine administration and not to a control group.…”
Section: C)mentioning
confidence: 99%
“…The decrease in blood flow velocity in cerebral and intestinal arteries following a high caffeine loading dose has been attributed to vasoconstriction, which may increase the risk of periventricular leukomalacia, hemorrhage, and necrotizing enterocolitis [38]. Owing to concern over the risk of cerebral and intestinal ischemia, Hoecker et al [40] investigated the use of a divided loading dose of two 25 mg/kg caffeine citrate doses separated by 4 h, and reported a decrease in cerebral blood flow velocity following the second dose, although blood flow velocity in intestinal arteries and left ventricular output were unaffected. It is well appreciated that high loading doses are more effective in the treatment of neonatal apnea, although further research is needed to develop an optimal loading-dose regimen.…”
Section: Resultsmentioning
confidence: 99%